Intelligent visual surveillance : 4th Chinese Conference, IVS 2016, Beijing, China, October 19, 2016, Proceedings /: 4th Chinese Conference, IVS 2016, Beijing, China, October 19, 2016, Proceedings. (2016) - Unknown
No abstract available